Back-calculate length-at-age estimates of Capoeta capoeta gracilis in dough stream, South Eastern Caspian Sea, Iran - Ranjbar, Khadijeh Shamekhi; Patimar, Rahman; Ghorbani, Rasoul; Kordjazi, Zia (Journal of Research in Biology, 2012)
This study was carried out between April and May 2010 and 2011 in Dough Stream, southern basin Caspian Sea. A total 130 individuals of C. c. gracilis were sampled to study back-calculation estimations. Fish ages were determined from operculum. The lengths of fish at previous ages (Back-calculated lengths) were estimated from operculum using back-calculation method. Back-calculations were based upon a linear regression model developed by Fraser and Lee. The calculated total length values for male and female ranged from 6.372-16.208 and 6.935-16.518 cm respectively. Calculated lengths were found smaller than the observed lengths